Portuguese Familial Hypercholesterolemia Study - Medeiros, A.M. (2012)
Familial hypercholesterolemia (FH) is an autossomal dominant disorder associated with high levels of plasma cholesterol and premature coronary heart disease (pCHD), with a frequency of 1/500. The major aim of the Portuguese FH Study is to identify the genetic cause of disease in patients with clinical diagnosis of FH so patients can receive counselling and treatment in time to prevent the development of pCHD. The clinical criteria used is from the Simon Broome Register (UK) and the genetic diagnosis was performed by the analysis of 18 fragments of the LDLR, 2 of the APOB and 5 of the PCSK9. These fragments are amplified by PCR and analysed by dHPLC and sequenced and MLPA to identify potential mutations. The Portuguese FH Study identified a genetic defect in 420 patients: 60 children, 122 adults (index patients) and 56 children, 182 adults (relatives), which represent only 2,1% of the FH cases estimated to exist in Portugal. The majority of index patients had a genetic defect in LDLR and 25% of the adults had pCHD. From the 238 relatives with FH identified by cascade screening, 13% of the adults had pCHD and 76 individuals in these families died from pCHD. The genetic diagnosis of FH confirms the clinical diagnosis based on plasma cholesterol levels and provides unequivocal diagnosis of patients and early identification of relatives. The counselling of these patients should result in appropriate treatment and adoption of a healthier lifestyle, in order to reduce their risk of CHD and decrease avoidable deaths